2020
DOI: 10.1017/qua.2020.73
|View full text |Cite
|
Sign up to set email alerts
|

Enviromagnetic study of Late Quaternary environmental evolution in Lower Volga loess sequences, Russia

Abstract: The late Quaternary development of the Lower Volga region of Russia is characterized by an alternating influence of marine and continental environments resulting from fluctuations in Caspian Sea level during the last glaciation. However, sediments deposited under continental conditions have received very little research attention compared to the under- and overlying marine deposits, such that even their origin is still in debate. Detailed magnetic mineralogical analyses presented here show clear similarities t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 127 publications
(216 reference statements)
0
17
0
1
Order By: Relevance
“…The new advances in rock magnetic methodologies and analytical techniques expand our ability to obtain important information on palaeoenvironmental change, including reconstruction of past geomagnetic field variations and environmental parameters, and understanding the processes of loesspalaeosol magnetic properties formation. Palaeoclimatic studies of the key loess-palaeosol sequences in the Chinese Loess Plateau (CLP), Central Asia, Danube Basin and East European Plain [Heller, Liu, 1984;Kukla et al, 1988;Forster et al, 1994;Jordanova, Petersen, 1999;Evans, Heller, 2001Rousseau et al, 2001;Buggle et al, 2009;Fitzsimmons et al, 2012;Marković et al, 2015;Necula et al, 2015;Bakhmutov et al, 2017;Chen et al, 2018;Song et al, 2018;Sümegi et al, 2018;Költringer et al, 2020;Bradák et al, 2021;Laag et al, 2021 and many others] have shown that rock magnetic palaeoenvironmental proxies, primarily magnetic susceptibility (MS), display strong similarities and can be correlated with the marine oxygen-isotope stages (MIS) [Shackleton et al, 1990;Lisiecki, Raymo, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…The new advances in rock magnetic methodologies and analytical techniques expand our ability to obtain important information on palaeoenvironmental change, including reconstruction of past geomagnetic field variations and environmental parameters, and understanding the processes of loesspalaeosol magnetic properties formation. Palaeoclimatic studies of the key loess-palaeosol sequences in the Chinese Loess Plateau (CLP), Central Asia, Danube Basin and East European Plain [Heller, Liu, 1984;Kukla et al, 1988;Forster et al, 1994;Jordanova, Petersen, 1999;Evans, Heller, 2001Rousseau et al, 2001;Buggle et al, 2009;Fitzsimmons et al, 2012;Marković et al, 2015;Necula et al, 2015;Bakhmutov et al, 2017;Chen et al, 2018;Song et al, 2018;Sümegi et al, 2018;Költringer et al, 2020;Bradák et al, 2021;Laag et al, 2021 and many others] have shown that rock magnetic palaeoenvironmental proxies, primarily magnetic susceptibility (MS), display strong similarities and can be correlated with the marine oxygen-isotope stages (MIS) [Shackleton et al, 1990;Lisiecki, Raymo, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Loess sediment in the mid-latitude of Eurasia provides an excellent sedimentary archive for understanding past climate and environmental changes in the continental interior (e.g., Rousseau et al, 2017Rousseau et al, , 2020Fenn et al, 2020;Fitzsimmons et al, 2020;Költringer et al, 2020;Song et al, 2021). In northern Iran, loess deposits are found in the so-called Northern Iranian Loess Plateau (NILP) and along the northern foothills of the Alborz Mountain range (NFAM).…”
Section: Introductionmentioning
confidence: 99%
“…The inconsistent changes in χ lf with pedostratigraphy, more complex pattern of χ fd %, and noncovariant relationship along the section between these two parameters may indicate that other processes affect the magnetic signal in the Beglitsa section. A recent enviromagnetic study in nearby Lower Volga loess deposits further east of Azov showed that there are also other factors, such as magnetic mineral dissolution by hydromorphic processes (Taylor et al, 2014), magnetic mineral destruction by strong weathering (Baumgart et al, 2013), magnetic mineral alteration induced by weak pedogenesis (Ma et al, 2013), and surface oxidation of coarse magnetic grains (Van Velzen and Dekkers, 1999;Buggle et al, 2014;Buggle et al, 2014;Stevens et al, 2020), controlling the magnetic signal in this region (Költringer et al, 2020). These processes do not always lead to magnetic enhancement but can cause dissolution and magnetic depletion of certain components, depending on the type of soils and the characteristics of the environment in which the paleosol formed (Bradák et al, 2021).…”
Section: The Last Glacial Loessmentioning
confidence: 99%